Bibliometric Analysis of Research Trends on Catch Handling on Purse Seine Vessels - Kasim, Muh Kasim; Rusli; Wahyuni Firman, Sri; Fattah , Nurlaeli (Hasanuddin University, 2025)
This study aims to analyze research trends related to the handling of catch on purse seine ships using a bibliometric approach. The fishing industry has a strategic role in food supply and global economic growth, where purse seine is one of the most commonly used fishing gear. The handling of catches on board ships has a great influence on fish quality, economic efficiency, and the sustainability of the fishery industry. However, there are still various challenges in the implementation of optimal storage methods, pre-processing, and sanitation and hygiene on board. Using data from the Scopus database, this study analyzes publication patterns, research collaborations, and main topics that develop in the study of handling catch on purse seine ships. The results of the analysis show that there is an increase in research interest in the aspects of storage technology and sustainability of fishery products. In addition, this study identifies a gap in studies related to technological innovations in handling fish on ships that are more efficient and environmentally friendly. The implications of this study provide insights for academics, industry practitioners, and policymakers to improve more effective and sustainable catch management systems.